2018
DOI: 10.1002/ejp.1279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated conditioning pain modulation in healthy volunteers

Abstract: Conditioning pain modulation can be assessed in 5-min intervals by cuff algometry with a fixed conditioning stimulus. Without applying conditioning stimuli the pain sensitivity of test-stimuli habituated. As a consequence, it can be speculated that the conditioning stimulus may negate the temporal habituation effects during repeated sessions, whereas this may not be the case for unconditioned stimuli. Applying both conditioned and unconditioned repeated test-stimuli may be a way to assess different parts of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…In line with a large body of evidence, this study showed pain reduction during conditioning pain modulation at grouplevel based on a cuff algometry CPM paradigm at baseline Hoegh et al, 2018;Kennedy et al, 2016;Petersen et al, 2017). The phasic cuff teststimuli paradigm (5 s pressure stimulations) showed excellent reliability.…”
Section: Conditioning Pain Modulationsupporting
confidence: 79%
See 4 more Smart Citations
“…In line with a large body of evidence, this study showed pain reduction during conditioning pain modulation at grouplevel based on a cuff algometry CPM paradigm at baseline Hoegh et al, 2018;Kennedy et al, 2016;Petersen et al, 2017). The phasic cuff teststimuli paradigm (5 s pressure stimulations) showed excellent reliability.…”
Section: Conditioning Pain Modulationsupporting
confidence: 79%
“…Particularly, the net CPM effect (i.e. the difference between the effect of repeated conditioned and repeated unconditioned test‐stimuli) is interesting since it may provide novel insights to the balance between facilitative and inhibitory descending control systems (Arendt‐Nielsen et al., ; Groves & Thompson, ; Hoegh et al., ). Accordingly, an exploratory analysis of the changes between the sessions ( Δ VAS) was conducted for the 1st and the 2–4th test‐stimuli, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations